Adaptive Douglas–Rachford Algorithms for Biconvex Optimization Problem in the Finite Dimensional Real Hilbert Spaces - Ming-Shr Lin; Chih-Sheng Chuang (Mathematics, 2024)
In this paper, we delve into the realm of biconvex optimization problems, introducing an adaptive Douglas–Rachford algorithm and presenting related convergence theorems in the setting of finite-dimensional real Hilbert spaces. It is worth noting that our approach to proving the convergence theorem differs significantly from those in the literature.